Enhanced thermoelectric figure of merit in p-type β-Zn4Sb3/Bi0.4Sb1.6Te3 nanocomposites. Issue 15 (29th January 2016) - Li, Yuanyue; Dou, Yunchen; Qin, Xiaoying; Zhang, Jian; Xin, Hongxing; Li, Di; Song, Chunjun; Zou, Tianhua; Liu, Yongfei; Li, Cong
Abstract : In Bi0.4 Sb1.6 Te3 -based composites incorporated with 1.3 vol% β-Zn4 Sb3 nanoparticles, figure of merit ZT = 1.43 is achieved at 443 K, which is ∼18% larger than that (=1.21) of Bi0.4 Sb1.6 Te3 matrix. Abstract : The thermoelectric properties of Bi0.4 Sb1.6 Te3 -based composites incorporated with β-Zn4 Sb3 nanoparticles are investigated in the temperature range from 300 K to 500 K. The results show that ∼5% increase in Seebeck coefficient and ∼32% reduction of lattice thermal conductivity at 443 K are concurrently realized in the nanocomposite system with 1.3 vol% of β-Zn4 Sb3, which originates from energy filtering effect as well as enhanced phonon scattering at dispersed nanoparticles and phase boundaries, respectively. As a result, the largest figure of merit ZT = 1.43 is achieved at 443 K for the sample with 1.3 vol% of β-Zn4 Sb3 nanoinclusions, which is ∼18% larger than that (=1.21) of the Bi0.4 Sb1.6 Te3 matrix.